A thermal shock-resistant porous ultra-high channel ceramic material and preparation method thereof

Through the combination of particle-grade spherical alumina, spherical magnesium hydroxide and spherical clay, combined with conventional plastic low-pressure extrusion molding, the problems of poor heat impact resistance and difficult production are solved, and high pore density and wall The preparation of thick and thin ceramic materials reduces production costs and improves heat shock resistance.

CN118993703BActive Publication Date: 2025-01-07SHANDONG AOFU ENVIRONMENTAL PROTECTION SCI & TECH +2
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411490021.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-01-07
Estimated Expiration
2044-10-24

AI Technical Summary

Technical Problem

The existing porous ceramic materials have poor heat impact resistance in frequent alternating heat and heat, and the preparation method is difficult to meet the requirements of high pore density and wall thickness, and are highly produced and have low efficiency.

Method used

Granular graded spherical alumina, spherical magnesium hydroxide and spherical clay are used as the main raw materials, and the process is made by mixing and stirring, dry mixing, wet mixing and vacuum, combined with conventional plastic low-pressure extrusion molding, forming porous ultra-high channel ceramics that are resistant to heat shock. Material.

Benefits of technology

It improves the stacking density and mud flowability of the ceramics, reduces the extrusion pressure, enhances the thermal conductivity and heat impact resistance of the material, and achieves the combination of high pore density and thin wall thickness, and is simple in production process and low in cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118993703B_ABST
    Figure CN118993703B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of porous ceramic materials, and in particular to a porous ultra-high channel ceramic material resistant to thermal shock and a preparation method thereof. The mud material of the material comprises a particle-graded spherical alumina powder, a spherical magnesium hydroxide powder and ball clay, and the ball clay comprises plastic illite and plastic disordered kaolinite; the particle size of the plastic illite and the plastic disordered kaolinite are both less than 2 μm. The method can improve the ceramic packing density and mud fluidity, and reduce the extrusion pressure; ball clay is used as a plasticizer to improve the plasticity and fluidity of the mud, so that the material has high thermal conductivity and good thermal shock resistance; the production process is simple and the cost is low.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of porous ceramic materials, and in particular to a thermal shock-resistant porous ultra-high channel ceramic material and a preparation method thereof. Background Art

[0002] Porous ceramics have ultra-high geometric specific surface area characteristics and are widely used. In order to ensure that the ultra-high channel microreactor does not crack during frequent hot and cold cycles, the ultra-high channel microreactor needs to have better thermal shock resistance.

[0003] The factors that have a greater impact on thermal shock resistance are mainly material selection and preparation methods. Currently, the most commonly used materials are ordinary aluminum oxide and magnesium hydroxide, and the thermal shock resistance of the prepared materials is difficult to meet the increasingly high requirements.

[0004] As for the preparation method, the plastic extrusion molding method is currently mainly used. However, as the pore density of porous ceramics increases and the wall thickness decreases, the difficulty of plastic extrusion becomes greater and greater, the extrusion pressure required by the extrusion equipment increases rapidly, and the requirements for the flow performance of the mud material are also getting higher and higher. The current mass production capacity of porous ceramics prepared by plastic extrusion molding is 900cpsi, the wall thickness is 50.8μm, and the molding extrusion pressure has reached ≥18MPa. The porous ceramics obtained by this preparation method have a low pass rate, and their thermal shock resistance and thermal conductivity are also difficult to meet the requirements.

[0005] In order to improve the above problems and increase the geometric specific surface area (ultra-high channel) of the microreactor, 3D printing is currently used to manufacture ultra-high channel honeycomb ceramics. However, due to the limitations of the preparation method, the maximum geometric specific surface area of ​​3D printing can reach 69.43 cm as described in patent CN 107056320B. 2 / cm 3 , the hole density is 2400 cpsi (holes per square foot), the wall thickness is 50.8μm (2mil), and 3D printing uses laser selective melting, which will bring problems of high cost and low efficiency. Summary of the invention

[0006] The technical problem to be solved by the present invention is to provide a thermal shock resistant porous ultra-high channel ceramic material and a preparation method thereof, so as to solve the problems of difficulty in plastic extrusion of porous ceramic materials, poor thermal shock resistance, high production cost, etc. in the prior art.

[0007] The technical solution of the present invention to solve the above technical problems is as follows:

[0008] The present invention provides a method for preparing a thermal shock-resistant porous ultra-high channel ceramic material. The ceramic material is prepared by using a mud material. The mud material comprises an inorganic component. The inorganic component comprises a particle-graded spherical alumina powder, a spherical magnesium hydroxide powder and a ball clay. The ball clay comprises plastic illite and plastic disordered kaolinite.

[0009] Wherein, the particle size D of the particle-graded spherical alumina powder is 50 0.5-5μm, particle size D 10 Greater than or equal to 0.1μm, particle size D 90 Less than or equal to 15μm, particle size D 100 Less than or equal to 20μm, particle size D 90 With particle size D 10 The ratio is greater than or equal to 4.0, and the mass percentage of aluminum oxide in the particle-graded spherical aluminum oxide powder is greater than or equal to 99.5%;

[0010] The particle sizes of the plastic illite and the plastic disordered kaolinite are both less than 2 μm.

[0011] Based on the above technical solution, the present invention can also be improved as follows.

[0012] Furthermore, the particle size D of the spherical magnesium hydroxide powder is 50 1-5μm, particle size D 10 Greater than or equal to 0.4μm, particle size D 90 Less than or equal to 10μm, particle size D 100 The diameter of the spherical magnesium hydroxide powder is less than or equal to 15 μm, and the mass percentage of magnesium oxide in the spherical magnesium hydroxide powder is greater than or equal to 61.0%.

[0013] Furthermore, the particle size D of the ball clay 50 1-4μm, particle size D 100 The particle size of the ball clay is less than or equal to 20 μm, and the mass percentage of silicon dioxide in the ball clay is greater than or equal to 43.5%, and the mass percentage of aluminum oxide is greater than or equal to 37.0%.

[0014] Furthermore, the mud material also includes a coupling agent, a binder, a lubricant and water.

[0015] Furthermore, in the inorganic component, the mass percentage of each component is: 91.60%-97.63% of the particle-graded spherical alumina powder, 0.37%-1.40% of the spherical magnesium hydroxide powder, and 2.0%-7.0% of the ball clay; based on the mass of the inorganic component as 100%, the mass percentage of the coupling agent is 0.5%-2.0%, the mass percentage of the binder is 4.0%-8.0%, the mass percentage of the lubricant is 2.0%-6.0%, and the mass percentage of water is 18.5%-21.0%.

[0016] Further, the following steps are included:

[0017] S1, mixing the particle-graded spherical alumina powder, the spherical magnesium hydroxide powder and the spherical clay with a coupling agent to obtain a powder;

[0018] S2, dry-mixing the powder with a binder, and then wet-mixing and kneading with a lubricant and water to obtain the mud;

[0019] S3, refining the clay material under vacuum conditions to obtain a clay segment with a plastic shape;

[0020] S4, extruding the mud segments and preparing them into a honeycomb structure, and then drying, cutting, sintering, and cold processing them in sequence to obtain the porous ultra-high channel ceramic material.

[0021] Further, in step S3, the vacuum degree of the vacuum condition is greater than or equal to -0.09 MPa.

[0022] Further, in step S4, the extrusion pressure is 6-11 MPa.

[0023] Furthermore, in step S4, the sintering temperature is 1500-1700° C., and the sintering holding time is 4-8 hours.

[0024] The present invention also provides a thermal shock-resistant porous ultra-high channel ceramic material, which is prepared by the above method. The porous ultra-high channel ceramic material has a pore density of 10,000-80,000 cpsi and a wall thickness of 1-2 mil.

[0025] The beneficial effects of the present invention are:

[0026] (1) The preparation method of the thermal shock resistant porous ultra-high channel ceramic material of the present invention uses spherical alumina and spherical magnesium hydroxide with particle grading as the main raw materials to improve the ceramic packing density and mud fluidity and reduce the extrusion pressure; uses ball clay as a plasticizer to improve the plasticity and fluidity of the mud; uses a silane coupling agent to perform surface modification and encapsulation on the above three main raw materials of spherical alumina, spherical magnesium hydroxide and ball clay to improve the mud fluidity;

[0027] (2) The preparation method of the thermal shock resistant porous ultra-high channel ceramic material of the present invention uses spherical magnesium hydroxide and spherical clay to form a cordierite binding phase, which densifies the high-aluminum porous ultra-high channel ceramic and improves the thermal conductivity. At the same time, the cordierite phase can reduce the thermal expansion coefficient of the high-aluminum porous ultra-high channel ceramic and improve the thermal shock resistance.

[0028] (3) The preparation method of the thermal shock-resistant porous ultra-high channel ceramic material of the present invention, which adopts the conventional plastic low-pressure (6-11MPa) extrusion molding preparation method to break through the technical barriers of high-pore density, ultra-thin-wall high-aluminum (alumina content ≥ 96%) porous ceramics, has a simple production process and low cost;

[0029] (4) The thermal shock resistant porous ultra-high channel ceramic material of the present invention has the advantages of high pore density and thin wall, so that its geometric specific surface area is large and the thermal shock resistance is high;

[0030] (5) The thermal shock-resistant porous ultra-high channel ceramic material of the present invention can be widely used in the pharmaceutical industry, environmental protection, fuel cells, thermoacoustic refrigeration, thermoacoustic power generation, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 The SEM image of the particle-graded spherical alumina powder in the method for preparing the thermal shock-resistant porous ultra-high channel ceramic material of the present invention;

[0032] Figure 2 This is a SEM image of the porous ultra-high channel ceramic material prepared in Example 7 in the method for preparing the thermal shock resistant porous ultra-high channel ceramic material of the present invention. DETAILED DESCRIPTION

[0033] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.

[0034] The preparation method of the thermal shock resistant porous ultra-high channel ceramic material of the present invention adopts mud material to prepare the material, wherein the mud material comprises inorganic components, the inorganic components comprise particle-graded spherical alumina powder, spherical magnesium hydroxide powder and ball clay, and the ball clay comprises plastic illite and plastic disordered kaolinite; wherein the particle size D of the particle-graded spherical alumina powder is 50 0.5-5μm, particle size D 10 Greater than or equal to 0.1μm, particle size D 90 Less than or equal to 15μm, particle size D 100 Less than or equal to 20μm, particle size D 90 With particle size D 10The ratio is greater than or equal to 4.0, and the mass percentage of alumina in the particle-graded spherical alumina powder is greater than or equal to 99.5%; the particle sizes of the plastic illite and the plastic disordered kaolinite are both less than 2 μm.

[0035] The preparation method of the thermal shock resistant porous ultra-high channel ceramic material of the present invention uses spherical alumina with a particle grading (D90 / D10≥4.0), the particle grading can form a larger packing density, which is conducive to the densification of ceramics and the improvement of thermal conductivity. The particle grading and the use of spherical alumina are conducive to the fluidity of the mud, reduce the extrusion pressure, and are conducive to the realization of plastic extrusion molding; the magnesium hydroxide used can be decomposed into active magnesium oxide at low temperature, which is conducive to reducing the problems that may occur after sintering, and is also conducive to forming a cordierite phase with spherical clay, reducing the thermal expansion coefficient of ceramics and improving the thermal shock resistance. The sphericalization of magnesium hydroxide can improve the fluidity of the mud, reduce the extrusion pressure, and is conducive to the realization of plastic extrusion molding; the spherical clay contains a large amount of plastic illite and plastic disordered kaolinite less than 2μm, which can improve the plasticity and fluidity of the mud.

[0036] Preferably, the particle size D of the spherical magnesium hydroxide powder is 50 1-5μm, particle size D 10 Greater than or equal to 0.4μm, particle size D 90 Less than or equal to 10μm, particle size D 100 The particle size of the spherical magnesium hydroxide powder is less than or equal to 15 μm, and the mass percentage of magnesium oxide in the spherical magnesium hydroxide powder is greater than or equal to 61.0%; the spherical magnesium hydroxide powder with the above particle size can further improve the fluidity of the mud and reduce the extrusion pressure, which is beneficial to improve the sintering success rate, and the mass percentage of magnesium oxide is higher, which is more conducive to forming a cordierite phase with the spherical clay.

[0037] Preferably, the particle size D of the ball clay is 50 1-4μm, particle size D 100 Less than or equal to 20μm, in the ball clay, the mass percentage of silicon dioxide is greater than or equal to 43.5%, and the mass percentage of aluminum oxide is greater than or equal to 37.0%; ball clay of this particle size can also further improve the performance of the mud.

[0038] Preferably, the mud also includes a coupling agent, a binder, a lubricant and water.

[0039] Further preferably, the coupling agent is a silane coupling agent, specifically one or more of KH550, KH560, and KH570. The silane coupling agent modifies the surface of the powder so that the surface of the material is coated with the silane coupling agent, which reduces the surface energy of the powder, improves the fluidity of the powder, is beneficial to the fluidity of the mud, and reduces the extrusion pressure.

[0040] Further preferably, the binder is an organic binder, specifically hydroxypropyl methylcellulose. Hydroxypropyl methylcellulose has a low viscosity, which is beneficial to increasing the water solubility rate of hydroxypropyl methylcellulose and improving the lubricity and fluidity of the slurry.

[0041] More preferably, the hydroxypropyl methylcellulose is prepared into a 2% by mass aqueous solution, and its viscosity is 200-600 mPa.s at 20°C.

[0042] Further preferably, the lubricant is a nano-scale polyethylene wax emulsion, which can be filled between the raw material particles to play a lubricating role, improve the fluidity of the mud, and reduce the extrusion pressure.

[0043] Further preferably, the particle size of the nano-scale polyethylene wax emulsion is 10-20 nm, and the solid content is 30-50%.

[0044] Preferably, in the inorganic component, the mass percentage of each component is: 91.60%-97.63% of the particle-graded spherical alumina powder, 0.37%-1.40% of the spherical magnesium hydroxide powder, and 2.0%-7.0% of the ball clay; based on the mass of the inorganic component as 100%, the mass percentage of the coupling agent is 0.5%-2.0%, the mass percentage of the binder is 4.0%-8.0%, the mass percentage of the lubricant is 2.0%-6.0%, and the mass percentage of water is 18.5%-21.0%.

[0045] The method for preparing the thermal shock resistant porous ultra-high channel ceramic material of the present invention comprises the following steps:

[0046] S1. Mix and stir the particle-graded spherical alumina powder, spherical magnesium hydroxide powder and spherical clay with a coupling agent to obtain a powder. The mixing and stirring can be performed using an inclined strong mixer for 1 to 2 hours.

[0047] S2, dry-mix the powder with the binder for 0.5-1 hour, and wet-mix and knead with the lubricant and water to obtain a mud material for 17-51 minutes.

[0048] S3. The clay material is refined under vacuum conditions to obtain clay segments with a plastic shape; the vacuum degree of the vacuum conditions is greater than or equal to -0.09 MPa.

[0049] S4, extruding the mud segments and preparing them into a honeycomb structure, and then drying, cutting, firing, and cold processing them in sequence to obtain a porous ultra-high channel ceramic material.

[0050] Preferably, the extrusion pressure is 6-11 MPa.

[0051] Preferably, the sintering temperature is 1500-1700° C., and the sintering holding time is 4-8 hours.

[0052] The thermal shock resistant porous ultra-high channel ceramic material of the present invention is prepared by the above method.

[0053] The thermal shock-resistant porous ultra-high channel ceramic material of the present invention has a pore density of 10,000-80,000 cpsi, a wall thickness of 1-2 mil, and a geometric specific surface area of ​​125.98 cm 2 / cm 3 -319.44cm 2 / cm 3 .

[0054] The thermal shock-resistant porous ultra-high channel ceramic material of the present invention can be used to prepare various microreactors with ultra-high geometric specific surface areas, such as in the pharmaceutical industry, environmental protection, fuel cells, thermoacoustic refrigeration, thermoacoustic power generation, etc. The diameter of the device made of these ceramic materials is 1-13 inches and the height is 2-12 inches.

[0055] There is no particular restriction on the shape of the honeycomb grid in the honeycomb structure. A single hole shape such as triangle, square, hexagon, etc. can be used, or multiple hole shapes such as square, hexagon, asymmetric, etc. can be used. It is not necessary to use a single hole shape in the honeycomb structure, and it is preferred to use, for example, square holes.

[0056] The present invention is illustrated below by means of specific examples.

[0057] Examples 1 to 10 are porous ultra-high channel ceramic materials prepared by the method of the present invention. Table 1 shows the property parameters of each component in the mud material of each example, the particle grading spherical alumina powder includes spherical alumina A1, spherical alumina A2, spherical alumina A3, the spherical magnesium hydroxide powder includes spherical magnesium hydroxide powder M1, spherical magnesium hydroxide powder M2, spherical magnesium hydroxide powder M3, and the ball clay includes ball clay B1, ball clay B2, and ball clay B3.

[0058] The comparative example uses a ceramic material prepared from 97% ordinary alumina, 1% calcium carbonate, 2% raw kaolin, 8% high viscosity (6000-10000 mPa.s) HPMC, and 6% soybean oil or tung oil.

[0059] Table 2 shows the mass percentages of the specific components of each embodiment. The mass percentages of the inorganic components (spherical alumina, spherical magnesium hydroxide, and spherical clay) are 100%, and the mass percentages of hydroxypropyl methylcellulose ether (HPMC), polyethylene wax emulsion, and water are all weight parts calculated in addition to the total weight of the inorganic components. The morphology of the porous ultra-high channel ceramic material prepared in Example 7 is shown in FIG. Figure 2Table 3 is a comparison of the material properties of Examples 1 to 10 and the comparative example.

[0060] Table 1 Shape parameters of inorganic components used in Examples 1 to 10

[0061]

[0062] Table 2 Mass percentage of specific components in each embodiment

[0063]

[0064] Table 3 Comparison of material properties of Examples 1 to 10 and Comparative Examples

[0065]

[0066] It can be seen from Examples 1-10 that as the amount of ball clay increases, the extrusion pressure decreases, and as the pore density increases, the wall thickness decreases, and the extrusion pressure increases, but all can meet the requirements of 6-11 MPa. As the pore density increases, the wall thickness decreases, and the extrusion qualified rate shows a downward trend, but all can reach more than 98.5%, which is much higher than the 96.24% of the comparative example; at the same time, as the alumina content increases, the thermal conductivity of the porous ceramic increases, but the thermal shock performance also decreases, but all meet the requirements of no cracking after three thermal shocks at 650°C, and the performance is much better than the comparative example.

[0067] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a porous ultra-high channel ceramic material resistant to thermal shock, characterized in that: The ceramic material is prepared by using mud, and the mud comprises inorganic components, and the inorganic components are composed of spherical alumina powder with particle grading, spherical magnesium hydroxide powder and ball clay, and the ball clay comprises plastic illite and plastic disordered kaolinite; Wherein, the particle size D of the particle-graded spherical alumina powder is 50 0.5-5μm, particle size D 10 Greater than or equal to 0.1μm, particle size D 90 Less than or equal to 15μm, particle size D 100 Less than or equal to 20μm, particle size D 90 With particle size D 10 The ratio is greater than or equal to 4.0, and the mass percentage of aluminum oxide in the particle-graded spherical aluminum oxide powder is greater than or equal to 99.5%; The particle sizes of the plastic illite and the plastic disordered kaolinite are both less than 2 μm; The particle size D of the spherical magnesium hydroxide powder 50 1-5μm, particle size D 10 Greater than or equal to 0.4μm, particle size D 90 Less than or equal to 10μm, particle size D 100 Less than or equal to 15 μm, the mass percentage of magnesium oxide in the spherical magnesium hydroxide powder is greater than or equal to 61.0%; The particle size D of the ball clay 50 1-4μm, particle size D 100 Less than or equal to 20 μm, in which the mass percentage of silicon dioxide is greater than or equal to 43.5%, and the mass percentage of aluminum oxide is greater than or equal to 37.0%; In the inorganic component, the mass percentage of each component is: the particle-graded spherical alumina powder 91.60%-97.63%, the spherical magnesium hydroxide powder 0.37%-1.40%, and the ball clay 2.0%-7.0%; The porous ultra-high channel ceramic material is formed by extrusion, and the extrusion pressure is 6-11MPa; The porous ultra-high channel ceramic material has a pore density of 10,000-80,000 cpsi and a wall thickness of 1-2 mil.

2. The method for preparing a thermal shock resistant porous ultra-high channel ceramic material according to claim 1, characterized in that: The mud material also includes a coupling agent, a binder, a lubricant and water.

3. The method for preparing a thermal shock resistant porous ultra-high channel ceramic material according to claim 2, characterized in that: Based on the mass of the inorganic component being 100%, the mass percentage of the coupling agent is 0.5%-2.0%, the mass percentage of the binder is 4.0%-8.0%, the mass percentage of the lubricant is 2.0%-6.0%, and the mass percentage of water is 18.5%-21.0%.

4. The method for preparing a thermal shock-resistant porous ultra-high channel ceramic material according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1, mixing the particle-graded spherical alumina powder, the spherical magnesium hydroxide powder and the ball clay with a coupling agent to obtain a powder; S2, dry-mixing the powder with a binder, and then wet-mixing and kneading with a lubricant and water to obtain the mud; S3, refining the clay material under vacuum conditions to obtain a clay segment; S4, extruding the mud segments and preparing them into a honeycomb structure, and then drying, cutting, sintering, and cold processing them in sequence to obtain the porous ultra-high channel ceramic material.

5. The method for preparing a thermal shock resistant porous ultra-high channel ceramic material according to claim 4, characterized in that: In step S3, the vacuum degree of the vacuum condition is greater than or equal to -0.09 MPa.

6. The method for preparing a thermal shock resistant porous ultra-high channel ceramic material according to claim 4, characterized in that: In step S4, the sintering temperature is 1500-1700° C., and the sintering holding time is 4-8 hours.

7. A porous ultra-high channel ceramic material resistant to thermal shock, characterized in that: The method is prepared by any one of claims 1 to 6.

Citation Information

Patent Citations

  • A Cordierite Honeycomb Ceramics and Its Application

    CN107056320B

  • Cordierite porous ceramic honeycomb articles with delayed microcrack evolution

    CN103298766A

  • Cordierite honeycomb ceramic carrier with excellent heat shock resistance and preparation method thereof

    CN110642613A